An experimentally-based molecular dynamics analysis of grain boundary migration during recrystallization in aluminum. (1st April 2022) - Li, Runguang; Homer, Eric R.; Hong, Chuanshi; Zhang, Yubin; Jensen, Dorte Juul
Abstract: Recent synchrotron X-ray measurements examined three-dimensional boundary migration during recrystallization [Scripta Mater 205 (2021) 114187]. To analyze possible correlations between grain boundary mobility and the observed heterogeneous boundary migration, molecular dynamics simulations were carried out. Migration of two selected boundary segments were simulated in both planar and spherical bicrystal atomistic models. These two segments were chosen because in the experiment one was observed to migrate much faster than the other. The simulations reveal that mobility cannot account for the experimentally observed heterogeneous migration. The result points to the possibility that recrystallization boundary migration strongly depends on features within the deformed microstructure. Graphical abstract: Image, graphical abstract